Supply chain management issues in the new era of collaboration and competition - Wang, William Y. C. 1974-.; Heng, Michael S. H. 1948-.; Chau, Patrick Y. K.; Gale Group (Hershey, Penn. Idea Group Pub., 2007)
"In the current business landscape, many business firms compete in one project and cooperate in another related project, and they do so at the same time. Even more interesting is that certain members of these firms are involved in both projects. This book examines this new business landscape."--Provided by publisher.
Implementing supply chain management in the new era : a replenishment framework for the supply chain operations reference model / William Y.C. Wang, Michael S.H. Heng, Patrick Y.K. Chau -- An investigation into the barriers to introducing virtual enterprise networks / Angela Lin, David Patterson -- Information flows in a New Zealand sheep meat supply chain / Andreas Schroeder, Beverley G. Hope -- Virtual integration : antecedents and role in governing supply chain integration / Jeffrey C F. Tai, Eric T.G. Wang, Kai Wang -- Trust and transparency in supply netchains : a contradiction? / Gert Jan Hofstede -- Integration of global supply chain management with small and medium suppliers / Asghar Sabbaghi, Ganesh Vaidyanathan -- Strategic alliances of information technology among supply chain channel members / H.Y. Sonya Hsu, Stephen C. Shih -- A process model of inter-organisational SCM initiatives adoption / Yu Ni Ham, Robert B. Johnston -- Factors affecting inter-organisational information management systems in Australian food processor chains / Christine Storer -- The application of soft systems methodology to supply chain management / Ross Smith, David Mackay, Graeme Altmann, Lucas Merlo -- Integrated e-enterprise supply chain security design and implementation / Stephen C. Shih, Michael Camarata, H. Joseph Wen -- Monitoring supply chain flows through improved performance measurement of extended processes / Marco Busi -- Supply chain risk management : a game theoretic analysis / Thorsten Blecker ... [et al.] -- Smart integrated e-operations for high-risk and technologically complex assets : operational networks and collaborative partnerships in the digital environment / Jayantha P. Liyanage, Mike Herbert, Jan Harestad.
Electronic reproduction.
Keywords: Business logistics; Electronic books